Landscape and the environment - Wilkoszewska, Krystyna (Polskie Studia Krajobrazowe, 2019)
The paper analyzes the concept of landscape and its various embodiments in art and nature. On the one hand, one can claim that our understanding of the landscape is constituted by conceptual oppositions like human/non-human, artifactual/natural, culture/nature; on the other, one may notice that landscapes occur in the space “between” these oppositions. Furthering this observation, I lodge an objection to the approach of certain exponents of environmental aesthetics who opt for replacing the notion of landscape by that of environment because I would argue that the former is still informative.